Communicating Corporate Responsibility to Investors: The Changing Role of the Investor Relations Function - Hockerts, Kai (Journal of business ethics, 2004)
Based on an inductive study we analyse the role of the investor relations (IR) function in the light of rising investor concern about corporate social responsibility (CSR). The study draws on interviews with IR professionals in twenty firms. It highlights their awareness of CSR issues as well as their assessment of concern among mainstream investors and socially responsible investors (SRIs). From these findings we develop suggestions on how the IR function is moving from a mere “broadcasting” mode regarding CSR issues into a much more interactive mode of relationship management.